Konsep Diri Remaja Dengan Orangtua Bercerai - Zain, Kharis Syarifudin; , Dr. Nisa Rachmah N.A., M.Si (2015)
Divorce happens by parents give a great influence in the development of adolescent self-concept in everyday life. This research was conducted with the aim of knowing the background of divorce of parents, know the factors that influence parents' divorce, knowing the consequences for adolescents of divorce of parents, and know the form of self-concept adolescents with divorced parents. This study used qualitative research methods. Subjects in the study were four early teens to late teens aged 12-21 years with divorced parents. The method used in data collection were interviews and observation. Interview results are then made in the form of the transcript and analyzed to discover the psychological meaning, a collection of units of meaning, concept mapping, and the deepest essence of the research results. This study found that adolescent self-concept with divorced parents have a tendency to evolve in a positive direction. They feel themselves comfortable in the family and social environment. Parents are married early teens when his family harmony. But after a long married parents of teens having an affair, doing domestic violence, and fight. Factors that make adolescents divorced parents is infidelity, domestic violence, and contention. Consequences received teens are feeling sad and disappointed. But some are happy and comfortable. Adolescent self-concept evolved towards the positive with this pecrceraian. From the physical form of positive informant, the informant can be accomplished in the academic and more eager to go to school. From the form of the positive psychological informant, the informant was happy because they do not see their parents fight back informants, and informants feel his life more comfortable and quiet. Their self-concept affects their attitudes toward interpersonal relationships. Keyword : Self Concept Teens, Parents' Divorce